Winning in life ([S. l.] : Nightingale Conant, 1992)
One of the world's greatest athletes - Walter Payton - shares his ideas for achieving greatness - for winning big on the field, in business and with your family. You will see how he judges business deals, assesses people, assembles his own team of top advisers, and sets goals
Bibliographical information is taken from the publisher's catalogue
Copy available in DVD format
Keywords: Achievement motivation; Motivation